A field‐deployable insulated isothermal RT‐PCR assay for identification of influenza A (H7N9) shows good performance in the laboratory. Issue 6 (5th September 2019) - Inui, Ken; Nguyen, Tung; Tseng, Hsin‐Jou; Tsai, ChuanFu Mark; Tsai, Yun‐Long; Chung, Simon; Padungtod, Pawin; Zhu, Huachen; Guan, Yi; Kalpravidh, Wantanee; Claes, Filip
Abstract: Background: Avian influenza A (H7N9) remains circulating in China. For countries at risk of introduction of H7N9, such as Vietnam, early detection of H7N9 virus is essential for the early containment of the virus. Insulated isothermal reverse transcriptase PCR (iiRT‐PCR) is a portable PCR system that can be deployed under field conditions to identify pathogens at the sampling site. Applying PCR at the sampling site will greatly reduce the time to obtain a diagnostic result which allows the veterinary authority to take immediate action to contain disease spreading. Objective: To determine analytical and diagnostic sensitivity and specificity of the portable iiRT‐PCR for H7N9 virus detection. Methods: A panel of 59 virus isolates, including H7N9, avian influenza viruses of subtype H1 to H13, swine and human influenza viruses, Newcastle disease virus, and infectious bursal disease virus, were tested by H7 and N9 iiRT‐PCR reagents, using probes and primers specific to H7 or N9, in comparison with laboratory‐based real‐time RT‐PCR assays to determine analytical sensitivity and specificity. Fifty oropharyngeal samples from experimentally infected chicken and ducks with H7N9 and 50 non‐infected control swabs were tested by the H7 iiRT‐PCR to determine diagnostic sensitivity and specificity. Results: The H7 and N9 iiRT‐PCR reagents yielded comparable levels of analytical sensitivity and specificity with real‐time RT‐PCR for the detection of H7N9 virus. Diagnostic sensitivity and specificity of H7 iiRT‐PCR were 98% and 100%, respectively. Conclusion: The observed high sensitivity and specificity of iiRT‐PCR for H7N9 detection show its potential for early detection of H7N9 in risk‐based surveillance.